2009
DOI: 10.1186/1471-5945-9-6
|View full text |Cite
|
Sign up to set email alerts
|

A population-based survey on tanning bed use in Germany

Abstract: Background: The suntanning industry has grown up over the last decade in Europe, mainly because tanned skin is considered socially desirable and attractive. Because of the potential negative impact of artificial tanning on public health, this study was to investigate tanning bed use behaviour, UV related risk perception and beliefs about tanning in the German population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 40 publications
4
33
2
3
Order By: Relevance
“…These last years, some studies have reported the frequency of tanning bed use in different contexts [9,10]. They reported the prevalence of tanning bed use, individual characteristics associated with this practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These last years, some studies have reported the frequency of tanning bed use in different contexts [9,10]. They reported the prevalence of tanning bed use, individual characteristics associated with this practice.…”
Section: Introductionmentioning
confidence: 99%
“…They reported the prevalence of tanning bed use, individual characteristics associated with this practice. For example, Börner et al [9], found positive relationships of appearance and health related beliefs with tanning bed use and some misconceptions in users about the positive effect of artificial UV radiation A systematic literature review reported that users are characterized by a lack of knowledge about health risks of UV, and prompted by the frequent use of sunbeds by friends or family members and the experience of positive emotions and relaxation by indoor tanning [11]. These characteristics are context dependant however [12], and it is important to study specific user profiles in the French context, given the fact that today, limited data are available to accurately describe the frequency of use of UV booths in France and user profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Auch diese Ergebnisse decken sich mit vorangegangen Studien [30 -34] . Positives Body Image, Attraktivit ä t und Wohlgef ü hl im Zusammenhang mit UV-Exposition haben in den letzten Jahren auch in Deutschland stark an Bedeutung gewonnen [40,41] . Fragt man nach der H ä ufi gkeit, mit der im Alltag an Risiken gedacht wird, so erweist sich, dass das Thema UV-Risiko im Alltagsdenken keinen dominanten Platz hat, wohl aber pr ä sent ist.…”
Section: Integratives Modellunclassified
“…Auch l ä sst sich nur ein geringer bzw. kein Zusammenhang zwischen Risikowahrnehmung und Expositionsverhalten feststellen, wie eine aktuelle Studie zu Solariennutzung in Deutschland belegt [41] . Br ä unung im Solarium ist allerdings eine Sonderform der UVExposition, da hier Attraktivit ä ts-und Wohlf ü hlaspekte eine besondere Rolle spielen.…”
Section: Integratives Modellunclassified
See 1 more Smart Citation